2013
DOI: 10.1128/cvi.00010-13
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4 Agonistic Antibody Promotes Innate Immunity against Severe Pneumonia Induced by Coinfection with Influenza Virus and Streptococcus pneumoniae

Abstract: cCoinfection with bacteria is a major cause of mortality during influenza epidemics. Recently, Toll-like receptor (TLR) agonists were shown to have immunomodulatory functions. In the present study, we investigated the effectiveness and mechanisms of the new TLR4 agonistic monoclonal antibody UT12 against secondary pneumococcal pneumonia induced by coinfection with influenza virus in a mouse model. Mice were intranasally inoculated with Streptococcus pneumoniae 2 days after influenza virus inoculation. UT12 was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…The TLR4 agonist MPLA is used as an adjuvant for the malaria vaccine (25), and its use in animal models as a booster for influenza (26) and HIV (27) vaccines, as well as its direct effects in a model of P. aeruginosa cutaneous-burn infection and bacteremia (13), has also been reported. Furthermore, we recently reported that UT12 inoculation improved the prognosis for secondary bacterial pneumonia following influenza (15). The anti-infective action of TLR agonists might involve immunological tolerance or activation, but the detailed mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The TLR4 agonist MPLA is used as an adjuvant for the malaria vaccine (25), and its use in animal models as a booster for influenza (26) and HIV (27) vaccines, as well as its direct effects in a model of P. aeruginosa cutaneous-burn infection and bacteremia (13), has also been reported. Furthermore, we recently reported that UT12 inoculation improved the prognosis for secondary bacterial pneumonia following influenza (15). The anti-infective action of TLR agonists might involve immunological tolerance or activation, but the detailed mechanisms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…UT12 can induce stimulatory signals comparable to those induced by LPS through TLR4/MD-2 and with 15-to 20-fold-greater potency by weight (14). Previously, we demonstrated that preadministration of UT12 increased protection against severe pneumococcal pneumonia induced by coinfection with influenza virus (15). As yet, however, the efficacy of TLR4 agonist therapy under conditions of established chronic infection and the associated mechanism remain unclear.…”
mentioning
confidence: 90%
“…IFN is essential for viral clearance, has been heavily studied since its discovery in 1957 [29], and has a complicated role in immunopathology (See [30] for a review). In recent mouse studies, animals, prior to infection, were exposed to synthetic or natural agonists of the Toll-Like Receptor pathways (specifically TLR3 and TLR4) that activate IFN production [27,28,31,32]. This pre-stimulation induced higher concentrations of IFN in lung epithelial cells, reduced virus titers and significantly improved infection outcomes in animals infected with highly pathogenic viruses.…”
Section: Immune Modulation For the Treatment Of Iav Infectionmentioning
confidence: 99%
“…P. aeruginosa was quantified by placing serial dilutions of the lung homogenates on LB agar plates and incubating them at 37°C under a 5% CO 2 atmosphere. For histopathological analysis, lung specimens were fixed in a 10% formalin-buffered solution, and then the lung tissue sections were paraffin embedded and were stained with hematoxylin and eosin (HE) using standard procedures (40).…”
Section: Methodsmentioning
confidence: 99%
“…BAL was performed using 1.0 ml of PBS, and the recovered fluid was pooled for each mouse. Total-cell counts were performed by Turk staining with a hemacytometer (40,41).…”
Section: Methodsmentioning
confidence: 99%